PENGARUH DETERMINAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN PROPERTI DI BURSA EFEK INDONESIA) - ., Murtianingsih (Department of Management, 2012)
MurtianingsihProgram Pascasarjana Magister Manajemen UMME-mail:Webmaster@unix.umm.ac.idABSTRACTThe research was to know the effect of profitability, firm size, liquidity, structure asset, businessrisk, and cost of capital to capital structure at property simultaneously listed on IndonesiaStock Exchange and to know the variable which have partial effect to the capital structure.The research was taken place at Indonesia Stock Exchange Economics Faculty ofMuhammadiyah University Malang. Respondent are 21 property companies listed in IndonesiaStock Exchange. Purposive sampling was used to determine companies during five-years.Secondary data was taken between the year of 2006 up to 2010. Multiple regression analysisused to know the effect of profitability, firm size, liquidity, structure asset, business risk, andcost of capital to capital structure with 5 % of significance. The result of simultaneously regression(F test) exemplify that the variable profitability, firm size, structure asset, growthopportunity, liquidity, the cost of capital, business risk had significant effects to the capitalstructure of 21 property companies listed in Indonesia Stock Exchange. While the test of partialregression (t test), for the variable of profitability, growth opportunity, liquidity, cost ofcapital had effects to capital structure of property companies listed in Indonesia Stock Exchange,except the firm size, business risk, structure asset have no significant effects to thecapital structure of the property companies.Keyword: Debt to equity ratio, company size, profitability, growth, business risk and asset structure,cost of capital, liquidity